Fibroepithelial stromal polyp of vagina in pregnancy - A mimicker - Gangadharan, Vandana; M, Sruthi; S, SHRILAKSHMI; P, HARIKA; P, DIVYA; KUMARI, KRISHNA (Indian Journal of Case Reports, 2022)
A rare mesenchymal neoplasm of the lower female genital tract, fibroepithelial stromal tumor, may be confused with other more aggressive lesions. The appearance in pregnancy may further complicate a normal vaginal delivery and lead to confusion with a more unfavorable diagnosis. Even on histological examination, it is pertinent to rule put other stromal tumors of the region. To avoid overdiagnosis, the pathologist must be aware of the specific histomorphology. We report a case of fibroepithelial stromal polyp in a 32-year-old pregnant woman as an incidental finding during a routine antenatal check-up.